Ragam hias busana tari klasik Jawa - Wulansari, Pramularsih (Kejawen, 2025)
This article describe about atribut ofJavanese classic dance. One of the reasons why the classic dance is not as well known as the younger Tari Srimpi because this ancient court dance could be performed only at royal weddings, commemoration of the throne and such special occasions. Since 1918 it is no longer danced exclusivelyinside the Yogya kraton wals dueto the foundation of the Krida Beksa Wirama dance school, founded by such court dance and gamelan experts as BPH Suryodiningrat, GPH Tejokusumo, KRT Jayadipura, KRT Wiraguna. Some how the old tradition is more or less still preserved due in part perhaps to tho difficulties of preparing such a perfomance. According to Javanese culture the Javanese classic dance have moral and spiritual teaching that used to life guidance.